2023
DOI: 10.1371/journal.pdig.0000171
|View full text |Cite
|
Sign up to set email alerts
|

Non-equivalent, but still valid: Establishing the construct validity of a consumer fitness tracker in persons with multiple sclerosis

Abstract: Tools for monitoring daily physical activity (PA) are desired by persons with multiple sclerosis (MS). However, current research-grade options are not suitable for longitudinal, independent use due to their cost and user experience. Our objective was to assess the validity of step counts and PA intensity metrics derived from the Fitbit Inspire HR, a consumer-grade PA tracker, in 45 persons with MS (Median age: 46, IQR: 40–51) undergoing inpatient rehabilitation. The population had moderate mobility impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Sufficient device wear time, defined as at least 10 h of wear time between 6:00 a.m. and 11:00 p.m., was computed and compared before and after rehabilitation stay discharge (Supplementary Appendix Table AS2). Details on the further processing of the PA tracker data in the BarKA-MS study can be found elsewhere (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sufficient device wear time, defined as at least 10 h of wear time between 6:00 a.m. and 11:00 p.m., was computed and compared before and after rehabilitation stay discharge (Supplementary Appendix Table AS2). Details on the further processing of the PA tracker data in the BarKA-MS study can be found elsewhere (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study participant wore an Actigraph GT3X (Manufacturing Technology, Inc., FL, USA), a threedimensional accelerometer validated for PwMS (28,29), on their non-dominant hip during their last week of rehabilitation and the first week back home. These data were published elsewhere (26,30).…”
Section: Wearable Device Measurementsmentioning
confidence: 97%
See 2 more Smart Citations
“…Activity sensors and Fitbit devices in particular have seen increasing adoption in MS research over the past years [ 11 ]; for example, such devices have been used to reduce sedentary behavior in persons with MS [ 12 ] or for remote monitoring of MS disability [ 13 ]. Despite the lower accuracy of Fitbit sensors at lower activity intensity [ 14 ] and slower walking speed [ 15 - 18 ], particularly relevant in the case of persons with MS, earlier studies have demonstrated the validity of Fitbit sensors in measuring step count [ 19 - 21 ]. These sensors enable individualized, passive, and inconspicuous monitoring of various metrics, including PA intensity and step counts, over an extended period of time [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%